THE USE OF NINJA APPS GAME TO ENRICH THE STUDENT'S WORD STOCKS - Henry Elisa; Tuti; Sijono (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
This research was carried out to help the students' problems in the classroom. Based on the pre-observation students tended to be passive and unmotivated and engaged in the learning process. Besides, the students also had a poor vocabulary. The researchers then applied Ninja Apps Game to solve the problems. The objectives of this research were to improve the students' participation and motivation through the implementation of Ninja Apps Game. This research employed classroom action research on thirty-eight students of the non-English study program. To collect the data the researchers used observation, interview, and measurement techniques. The instrumentations used were an observation sheet, field note, test, and interview guidelines. The findings showed that Ninja Apps Game effectively improved the students' participation, motivation, and vocabulary mastery. The students were happy, relaxed, and enjoyed the implantation of Ninja Apps Game. The finding of this research brings a new perspective to the teaching and learning process, especially in teaching vocabulary. Ninja Apps Game provides some activities which reflect cooperation, competition, and also discipline in using time.